Inhibition of purine nucleoside and nucleobase transporters by tyrosine kinase inhibitors - Nayiar Shahid; Chan H. Kim; Kerrylei B. Jabilona; Khanh H. Nguyen; Nicholas M. Ruel; James R. Hammond (PLoS ONE, 2026)
Tyrosine kinase inhibitors (TKI) are often used in combination with other chemotherapeutic nucleoside/nucleobase analogues, such as gemcitabine and 6-mercaptopurine, in the treatment of various cancers. Past studies have shown that several TKI inhibit the cellular uptake of nucleoside analogues by the equilibrative nucleoside transporter subtype 1 (ENT1), and suggest that TKI may also inhibit other related nucleoside and nucleobase transporters such as ENT2 and the equilibrative nucleobase transporter (ENBT1). To assess this possibility in a controlled manner, we have compared the ability of a series of TKI to inhibit each of these transporters in HEK293 cells that have been genetically modified to express either ENT1, ENT2 or ENBT1 in isolation, and on ENBT1 natively expressed in the chronic myeloid leukemia cell line K562. All TKI tested inhibited ENT1 and ENT2 with K i values ranging from 1 to 30 µM, typically with higher affinities for ENT1 than for ENT2. Gefitinib, which was one of the most effective inhibitors of ENT1, also inhibited ENBT1 with a similar affinity. The loss or gain of these transporters had no impact on the ability of gefitinib to directly affect cell viability, indicating that they were unlikely to be involved in the cellular uptake of the TKI. These data suggest that TKI inhibit multiple purine transporters, likely via interactions with their common purine ring binding domain. However, interactions between TKI and other nucleoside/nucleobase analogue drugs that are substrates for these systems are not likely to be a significant concern at the doses commonly used therapeutically.